Stimulation of triple negative breast cancer cell migration and metastases formation is prevented by chloroquine in a pre-irradiated mouse model. Issue 1 (December 2016) - Bouchard, Gina; Therriault, Hélène; Geha, Sameh; Bérubé-Lauzière, Yves; Bujold, Rachel; Saucier, Caroline; Paquette, Benoit
Abstract Background Some triple negative breast cancer (TNBC) patients are at higher risk of recurrence in the first three years after treatment. This rapid relapse has been suggested to be associated with inflammatory mediators induced by radiation in healthy tissues that stimulate cancer cell migration and metastasis formation. In this study, the ability of chloroquine (CQ) to inhibit radiation-stimulated development of metastasis was assessed. Methods The capacity of CQ to prevent radiation-enhancement of cancer cell invasion was assessed in vitro with the TNBC cell lines D2A1, 4T1 and MDA-MB-231 and the non-TNBC cell lines MC7-L1, and MCF-7. In Balb/c mice, a single mammary gland was irradiated with four daily doses of 6 Gy. After the last irradiation, irradiated and control mammary glands were implanted with D2A1 cells. Mice were treated with CQ (vehicle, 40 or 60 mg/kg) 3 h before each irradiation and then every 72 h for 3 weeks. Migration of D2A1 cells in the mammary gland, the number of circulating tumor cells and lung metastasis were quantified, and also the expression of some inflammatory mediators. Results Irradiated fibroblasts have increased the invasiveness of the TNBC cell lines only, a stimulation that was prevented by CQ. On the other hand, invasiveness of the non-TNBC cell lines, which was not enhanced by irradiated fibroblasts, was also not significantly modified by CQ. In Balb/c mice, treatment with CQ prevented the stimulation of D2A1 TNBC cell migration in the pre-irradiated mammary gland, and reduced the number of circulating tumor cells and lung metastases. This protective effect of CQ was associated with a reduced expression of the inflammatory mediators interleukin-1β, interleukin-6, and cyclooxygenase-2, while the levels of matrix metalloproteinases-2 and −9 were not modified. CQ also promoted a blocking of autophagy. Conclusion CQ prevented radiation-enhancement of TNBC cell invasion and reduced the number of lung metastases in a mouse model.